YOU CAN GO HOME AGAIN: PLINY THE YOUNGER WRITES TO COMUM. (20th December 2018) - CARLON, JACQUELINE M.
Abstract: Despite his absence from his home town, Pliny's ongoing relationship with Comum and its residents is readily apparent in his letters. Careful examination of his donations to his patria and his correspondence with friends and family residing there makes it clear that Pliny's home town does not just serve as an autobiographical vehicle in the letters but is also one of his most important audiences. He presents Comum as a locus amoenus, an ideal place for him to enjoy the kind of refined retirement he so often praises in his letters.